Classroom assessment in action - Shermis, Mark D. (Unites States of America : Rowman & Littlefield, 2011)
Classroom Assessment in Action clarifies the multi-faceted roles of measurement and assessment and their applications in a classroom setting. Comprehensive in scope, Shermis and Di Vesta explain basic measurement concepts and show students how to interpret the results of standardized tests. From these basic concepts, the authors then provide clear and ordered discussions of how assessment and instruction is integrated into a functional process to enhance student learning. Guidelines are set forth for constructing various common assessments. Procedures are laid out to evaluate and improve assessments once they are constructed. Ultimately, the authors shed light on the myriad of factors that impact test score interpretation.
1 Orientation to Assessment -- 2 Planning Assessments -- 3 Observation: Bases of Assessment -- 4 Formative Assessment: Using Assessment for Improving Instruction -- 5 Performance Assessment -- 6 Developing Objective Tests -- 7 Developing Subjective Tests -- 8 Selecting Standardized Tests -- 9 Technology in Assessment -- 10 Improving Tests -- 11 Domain-Specific Assessment and Learning -- 12 Grading; 13 Supplementary Assessments of Individual Differences -- 14 High-Stakes Testing: Policy and Accountability -- 15 Assessment and Best Practices .
Includes index.
Keywords: EDUCATIONAL MEASUREMENTS